Perspective on the Caribbean public sector : draft - Knight, Gloria...[et al] ([World Bank] WashingtonUS, 1996)
Provides an historical overview of the public sector in the Caribbean. Looks at the constitutional and legal framework of the executive, parliament and public enterprises, as well as at the regional public sector institutions. Focuses on human resources development and the role of the public sector in the provision of economic infrastructure. Examines the regulation of the financial sector.